Sustainable Development and Planning IV : Volume 2. - Brebbia, C. A.; Neophytou, M.; Beriatos, Ēlias; Iōannou, I. (WIT transactions on ecology and the environment, 2009)
The Conference addresses the subjects of regional development in an integrated way in accordance with the principles of sustainability. It has become apparent that planners, environmentalists, architects, engineers, policy makers and economists have to work together in order to ensure that planning and development can meet our present needs without compromising the ability of future generations. Effective strategies for management should consider planning and regional development, two closely related disciplines, and emphasise the demand to handle these matters in an integrated way. This con.